Long Term Care Insurance with State-Dependent Preferences - Philippe De Donder; Marie-Louise Leroux (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
We study the demand for actuarially fair Long Term Care (LTC hereafter) insurance in a setting where autonomous agents only care for daily life consumption while dependent agents also care for LTC expenditures. We assume that dependency decreases the marginal utility of daily life consumption. We first obtain that some agents optimally choose not to insure themselves, while no agent wishes to buy complete insurance. We then show that the comparison of marginal utility of income (as opposed to consumption) across health states depends on (i) whether agents do buy LTC insurance at equilibrium or not, (ii) the comparison of the degree of risk aversion for consumption and for LTC expenditures, and (iii) the income level of agents. Our results then o↵er testable implications that can explain (i) why few people buy Long Term Care insurance and (ii) the discrepancies between various empirical works when measuring the extent of state-dependent preferences for LTC.
Keywords: 330